PROPOSIÇÃO DE MEDIDAS DE GESTÃO, ECO-EFICIÊNCIA E SUSTENTABILIDADE EM USINAS TERMOELÉTRICAS. ESTUDO DE CASO DA UTE MARIO LAGO, MACAÉ, RJ - Silva, Waldemir Ferreira da (2009)
This dissertation had an objective to evaluate the production, management, ecoefficiency and sustainability of a Natural Gas Thermo Power Plant, and special carrying out a case study of Mario Lago Power Plant, located in the City of Macaé, RJ. A case study at the Thermo Power Plant had been carried out considering the application of the environmental laws, the implementation of Environmental, Health and Safety Management Systems. The research carried out in this work considered literature research, review of the legislation, use of internet tools and the available material in the Thermo Power Plant, as several reports, available standards, software and others. In this study, were proposed eco-efficiency measures related to the sustainable operation of the Natural Gas Power Plant, such as: substitution of chemicals to avoid hazards to the environment, technical and economic viability study for closing of 4 turbines in combined cycle, among others. Finally, the importance of a management system with focus in sustainability and production for a Natural Gas Power Plant was evaluated and it was commented the essential tools to promote eco-efficiency and continuous improvement.